PEMBANGUNAN HUTAN DI PROVINSI RIAU SUATU STUDI STRATEGI PENGENDALIAN GREENPEACE DALAM PENGAWASAN HUTAN - Putri Lindung Bulan; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Greenpeace is an INGO (International Non-Government Organization) which is an independent organization financially and organisationally. Greenpeace is an environmental organization that is campaigning. Activities undertaken by Greenpeace is soft activity and are NVDA (Non Violent Direct Action) that perform direct action in accordance with the issue and without violence. Public campaign by Greenpeace in Indonesia include, Sea, Forest, Toxic Waste and Renewable Energy. However, for in Riau Province Alone most focused campaign is menngenai Forest.Problems of forest in Riau Province is very difficult to find a way out to block the opening of new land by burning the land every year. Greenpeace as environmental organizations feel the need to participate in order to save the remaining forests and voice to the burning of land that they are doing is wrong. Seeing the weakening penngawasan of government and legal regulations on forest make some menngeluarkan Greenpeace campaign on forests of Riau and Sumatra. However, due to the government or organization Greenpeace is not bound to make limited motion governance authority decisions taken by Greenpeace.Keywords: Greenpeace, Forest, Riau Provin